Open-Door Laminoplasty Using Lateral Mass Anchoring Screws and Nonabsorbable Sutures in Patients with Multilevel Cervical Myelopathy - Cha, Jae-Ryong (Clin Orthop Surg, 2020)
BACKGROUD: The purpose of this study was to evaluate the clinical usefulness of open-door laminoplasty using lateral mass anchoring screws and nonabsorbable sutures (ODLLM) for multilevel cervical myelopathy. METHODS: We retrospectively studied 30 patients who underwent ODLLM. Clinical evaluations were performed using a visual analog scale (VAS), Japanese Orthopaedic Association (JOA) score, and Neck Disability Index (NDI) preoperatively, at 1 year postoperatively, and at the last follow-up. Radiographic evaluation was done using cervical spine radiographs to measure changes in the lordotic angle and range of motion (ROM) preoperatively, at 1 year postoperatively, and at the last follow-up and computed tomography at 1 year postoperatively to measure the opening angle and anteroposterior diameter of the spinal canal. RESULTS: Significant improvement in VAS, JOA, and NDI was seen overall at 1 year after operation. However, there was no significant difference between 1 year after operation and the last follow-up. There were no significant changes in the lordotic angle and neck ROM. The mean opening angle of the opened lamina was measured as 39.04°. The mean anteroposterior diameter was significantly increased from 7.51 ± 1.79 mm before surgery to 13.98 ± 1.80 mm at 1 year of operation. Complications such as laminar reclosure and screw loosening were not observed in all cases. CONCLUSIONS: The ODLLM was technically easy to perform and showed good results comparable to those of conventional techniques. It can be suggested that ODLLM is an appropriate treatment option for multilevel cervical myelopathy.